Job loss in the age of Artificial Intelligence (AI) / Jamilah Laidin, Nor Azira Ismail and Shahiszan Ismail - Laidin, Jamilah; Ismail, Nor Azira; Ismail, Shahiszan (Universiti Teknologi MARA, Kedah, 2023)
As technology evolves, we are seeing more and more ways in which Artificial Intelligence (AI) is being integrated into robots, and today we will look at some of the most interesting and innovative examples of this technology. Schwab and Zahidi (2023), reported that demand for AI and Machine Learning Specialists is predicted to increase by 40%, or 1 million jobs, as AI and machine learning drive the continuing industrial revolution. AI refers to the ability of machines to perform tasks that would typically require human intelligence, such as learning, problem solving, and decision-making. Because of recent developments in AI technology, a growing number of robots are beginning to incorporate AI into their operations. As the field of AI continues to improve, we may anticipate the creation of robots that are even more advanced and intelligent. These robots will be capable of performing tasks that are currently impossible for them to do. This integration allows robots to perform tasks that were previously considered too complex for them to handle. For example, robots can now recognize speech and respond to commands, navigate complex environments and even make decision based on data like ChatGPT. We have seen how AI is being integrated into robots and the applications it has across various industries nowadays. AI has sparked discussions about its influence on employment. While AI brings tremendous opportunities and advancements across industries, concerns about job displacement have also emerged.